The development of rank order and aggressiveness in a group of juvenile Greylag Geese - Stahlberg, Britt-Marie (Wildfowl, 1974)
In a group of five incubator-hatched goslings, which were human-imprinted, fights were fairly common and a linear rank order was established. Greeting, appeasement and redirected behaviours are described. Different results obtained in other studies are discussed.